Effect of music-based movement therapy on the freezing of gait in patients with Parkinson’s disease: A randomized controlled trial - Li, Kun-peng; Zhang, Zeng-qiao; Zhou, Zong-lei; Su, Jian-qing; Wu, Xian-hua; Shi, Bo-han; Xu, Jian-guang (Frontiers in Aging Neuroscience, 2022)
Objective：To explore the effect of music-based movement therapy (MMT) on PD with FOG Methods: This was a prospective randomized controlled study. 81 participants were randomly divided into MMT group (N=27), exercise therapy group (ET, N=27), and control group (N=27). Participants in the MMT group were treated with MMT five times (1 hour each time) every week for 4 weeks. Subjects in the ET group were manipulated the same way as in the MMT group, but there was no music. Routine rehabilitation treatment was performed in all groups. The primary evaluation index was the change of FOG. Secondary evaluation indicators included FOG-Questionnaire and the motor function. Results: After four weeks of intervention, the double support time (P=0.002), the cadence (P=0.005), the max flexion of knee in stance (P=0.010), the max hip extension (P<0.001), the flexion moment of knee in stance (P=0.009), the comprehensive motor function (UPDRS Part III gait-related items total score: P=0.002; Arising from chair: P=0.005; Freezing of gait: P=0.001; Postural stability: P=0.003; Posture: P=0.005; MDS-UPDRS Part II gait-related items total score: P=0.003; Getting out of bed, a car, or deep chair: P=0.002; Walking and balance: P=0.001; Freezing: P=0.003) and the FOG-Q (P=0.006) in the MMT group was lower than that in control group and ET group. The gait velocity (P=0.015), the max ankle dorsiflexion in stance (P<0.001), ankle ROM during push-off (P<0.001), ankle ROM over gait cycle (P<0.001), the knee ROM over gait cycle (P=0.001), the max extensor moment in stance (ankle:P=0.011; knee: P=0.016) in the MMT group was higher than that in control group and ET group. However, no significant difference was reported between the control group and ET group (P>0.05). The stride length (P=0.030) and hip ROM over gait cycle(P=0.031) in the MMT group was higher than that in control group, the max knee extension in stance (P=0.001) in the MMT group was lower than that in control group. Nevertheless, there was no significant difference between the ET and MMT group (P>0.05) or the control group (P>0.05). Conclusion: MMT improved gait disorders in PD patients with FOG, thereby improving their comprehensive motor function.